El sentido de la vida: un aporte de la psicología a la educación religiosa escolar - John Freddy, Bedoya (Educación, 2017)
This article intends to raise, within the aims of School`s Religious Education, helping students to focus their will to meaning, to the giving of self, transcending his own self and selfishness, in favor of another, or other and even a cause, like Victor Frankl as suggested in theory, called logotherapy, which develops throughout his work. The methodology used has come from reading some of his works and inquiry respect to studies that the author raises about the meaning of human life, which necessarily involves suffering. They have as a backdrop the guidelines, standards and skills own area; worth noting that it has been contextualized in the Christian religious acts, because it is the most prevalent in our culture. It is the responsibility of Religious Education School and particularly educators in this area proposing, in an ethical manner, conscientiously and responsibly, developing life projects of students, guiding them and helping them in their concerns and existential voids, to make the right decisions, so that each appropriates in a responsible and aware of what is going to perform and achieve, foresight, short and long term.